Harmonization of Fines (Taʿzir), Compensation (Ta’wiḍh) and the Financial Information Service System (SLIK) in Sharia Financial Institutions as Cumulative Sanctions for Defaulting Debtors: Analysis of DSN-MUI Fatwa and POJK - Nur Irmandi; Abdal; Syamsurijal; Ratna Istianah (Mabahits Al-Uqud, 2025)
This study analyzes penalties (ta’zir) and compensation (ta’wiḍh) in Islamic financial institutions, as well as the role of the Financial Information Service System (SLIK) as a form of cumulative sanctions for defaulting debtors. This study focuses on a crucial research gap: the lack of a harmonized framework between sharia sanctions (DSN-MUI) and reputation sanctions (OJK), which has the potential to cause injustice due to cumulative sanctions for debtors. Focusing on DSN-MUI Fatwas No. 17/2000, No. 43/2004, No. 129/2019, and OJK Regulation No. 18/POJK.03/2017, this study uses a normative juridical method. This study finds that the DSN-MUI fatwas affirm the principle of proportionality by limiting ta’wiḍh to real costs and establishing ta’zir as a disciplinary instrument. However, their implementation in the field shows variation. Integration with reputation sanctions through SLIK, while strengthening oversight, creates a dual sanctions regime that raises issues of fairness. As an original contribution, this article proposes a “tiered sanction model” as a new solution for harmonization. This study concludes that the current dualistic system, without harmonization, systematically disadvantages debtors and requires an immediate regulatory review.